Innovation Barriers, Implementation Open Innovation , And Its Implications On the Performance of Small and Medium Enterprises in Indonesia - Jumi Apriza (PT SOLUSI EDUKASI BERDIKARI, 2025)
Small and Medium Enterprises (SMEs) play a role important in economy national Because capable adapt with change and create field work . However , SMEs often face various obstacle in innovate . Research This aim analyze influence obstacle innovation to implementation innovation open as well as the implications to performance SME innovation in Indonesia. Obstacles innovation shared become four group , namely market and institutional barriers , finance , behavior employees and organizations , as well as knowledge and work same . Research results show that market and institutional barriers as well as obstacle behavior employees and organizations influential positive to innovation open , whereas obstacle finance as well as obstacle knowledge and work The same No influential significant . In addition , innovation open influential positive to performance SME innovation . Findings This confirm that innovation open become an important strategy for SMEs to increase Power competition in environment dynamic business .​